The relationship of sleep with temperature and metabolic rate in a hibernating primate. - Andrew D Krystal (Public Library of Science (PLoS), 2013)
Study objectives It has long been suspected that sleep is important for regulating body temperature and metabolic-rate. Hibernation, a state of acute hypothermia and reduced metabolic-rate, offers a promising system for investigating those relationships. Prior studies in hibernating ground squirrels report that, although sleep occurs during hibernation, it manifests only as non-REM sleep, and only at relatively high temperatures. In our study, we report data on sleep during hibernation in a lemuriform primate, Cheirogaleus medius. As the only primate known to experience prolonged periods of hibernation and as an inhabitant of more temperate climates than ground squirrels, this animal serves as an alternative model for exploring sleep temperature/metabolism relationships that may be uniquely relevant to understanding human physiology. Measurements and results We find that during hibernation, non-REM sleep is absent in Cheirogaleus. Rather, periods of REM sleep occur during periods of relatively high ambient temperature, a pattern opposite of that observed in ground squirrels. Like ground squirrels, however, EEG is marked by ultra-low voltage activity at relatively low metabolic-rates. Conclusions These findings confirm a sleep-temperature/metabolism link, though they also suggest that the relationship of sleep stage with temperature/metabolism is flexible and may differ across species or mammalian orders. The absence of non-REM sleep suggests that during hibernation in Cheirogaleus, like in the ground squirrel, the otherwise universal non-REM sleep homeostatic response is greatly curtailed or absent. Lastly, ultra-low voltage EEG appears to be a cross-species marker for extremely low metabolic-rate, and, as such, may be an attractive target for research on hibernation induction.